الأبيات غير المنسوبة لقائل في كتاب (المقتضب) للمبّرد ت (285هـ) (Journal of Faculty of Education, 2022)
هدفت الدراسة إلي بيان جوانب أدبيّة  في أبيات الاستشهاد التي لم ينسبها المبرّد  إلي قائليها في كتابه(المقتضب )، إذ تنصّب الدراسات في مثل هذه المؤلفات  بما فيها الشواهد الشعريّة علي  تبيّين القاعدة النحويّة  وبيان ووجوه الاختلافات فيها ولا تكترث كثيراً بدراسة  الشواهد الشعريّة من حيث  قضايا الشعر وما يتعلّق بها ؛مع أهميّتها في فهم القاعدة النحويّة وترسيخها .اتبعت الدراسة المنهج الوصفي. أظهرتنتائج    الدراسة  الآتي : إنّ عدم نسبة الأبيات إلي قائليها  ليس غريباً أو بدعاً  علي النحاة و اللغويين  القدامي  ربما لشهرة ما يستشهدون به من شعر إذ من كان قبلهم يعتمد كليّاً علي الرواية والاستظهار ، كما أنّ  من جاء بعد هولاء المؤلفين الذين درسواهذه المؤلفات  والمحققين الذين ساهموا في إخراجها بصورتها الحالية اهتموا بنسبة الأبيات إلىقائليها ،وتوضيح بعض  القضايا الأدبيّة فيها  إلّا إنّ هذا العمل والمجهود المبذول لم يشمل كلّ الأبيات إذ ظلت بعض الأبيات عصيّة علي العزو لقائل؛ فبقيت على ماهي عليها، وبعض الأبيات متنازعة النسبة ( منسوبة لاكثر من قائل) . نلحظ أنّ وجوه الاستشهاد  في جلِّ هذه الأبيات أتت بها ضرورات الشعر  مع ملاحظة قلّة التعليقات المتعلقّة بالنقد والبلاغة في الأبيات غير المنسوبة لقائل التي احتواها كتاب(المقتضب).This study aimed at illustrating some artistic aspects of some poetic quotations that Almobbarid cited without mentioning their poets in his book (Almogtadab). Many studies focused on such books along with the poetic quotations cited in so as to explain the grammatical rules and their differences thought no focus on is given to poetic citation as poetic subjects the related topics despite their importance in understanding and establishing the grammatical rules. The study followed the descriptive method. Thefindings of the study showed that citing poetic quotations without mentioning their authors -maybe due the reputability of what they cite - is not novel to the former grammarians because the poets preceded them entirely depended on narration and recitation.  Then, the authors as well as the investigators, who came later and who studied these books and made it like what it looks today, attributed the quotation to the their authors and clarified the artistic values imbedded in. Despite, the effort exerted by authors and investigators’ some quotations were not easily attributed to their original authors while some others were attributed to more than an author. It is also observed that the aims of the majority of these quotations were necessitated by the needs of poetry. This beside the fewness in the number of comments related to rhetoric and criticism of unattributed quotations cited in Almogtadab.
Keywords: جوانب أدبيّة في أبيات الاستشهاد; المبرّد; الشواهد الشعريّة